The Academic Entrepreneur: Myth or Reality for Increased Regional Growth in Europe? - Erdős, Katalin; Varga, Attila (PTE KTK Műhelytanulmányok, 2022)
Knowledge flows from universities to the regional economy can take different forms ranging from formal research collaborations to consultancy and informal personal connections. One of the knowledge communication channels drawing substantial interest of both researchers and regional policy makers is academic spin-off firm formation. According to the concept of the “academic entrepreneur” (Etzkowitz) university spin-off firm formation has grown naturally from the academic culture of the US where professors traditionally behave very much like entrepreneurs while setting up and maintaining research labs, hiring research assistants, “marketing” research results in conferences and publications or networking with colleagues and funding agencies. Spinning off a company is just a step forward from such entrepreneurial tasks of academics. Thus according to this concept academic motivations are main drivers in university spin-off firm formation in the US. Despite this challenging view the empirical literature pays relatively little attention to the particular “academic” features of university spin-offs and rarely considers the specificities of university entrepreneurship most notably the role of scientists as entrepreneurs. Empirical evidence suggests that Europe performs less successfully than the US in transferring knowledge from university labs to the regional economy via spin-off companies. One potential reason behind this difference is that institutions that determine the continental European research system hold back the emergence of academic entrepreneurs. Thus it is the main research question in our paper whether those specific “academic” drivers behind university spin-off firm formation are present at all in the continental European context. The related question is whether professional characteristics of the academics, their social capital, the norms of academia and the academic and business environment support or hinder these academic motivations? This paper is based on interviews carried out with university researchers who actively participate in firm formation in Hungary. Hungary is an excellent European case since the features of its university system are rooted in the continental (mainly German) tradition, but it also inherits some characteristics from the even more centralized socialist (soviet) tradition.